2016
DOI: 10.1016/j.yjmcc.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Roles and regulation of protein phosphatase 2A (PP2A) in the heart

Abstract: Reversible protein phosphorylation is central to a variety of cardiac processes including excitation-contraction coupling, Ca2+ handling, cell metabolism, myofilament regulation, and cell-cell communication. While kinase pathways linked with elevated adrenergic signaling have been a major focus for the cardiovascular field over the past half century, new findings support the critical role of protein phosphatases in both health and disease. Protein phosphatase 2A (PP2A) is a central cardiac phosphatase that reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 85 publications
0
50
1
Order By: Relevance
“…Joe et al () suggested that TTP is effective at inducing inflammatory cytokines such as ILs and TNF‐α. PP2A may induce anti‐apoptotic and anti‐inflammatory activity in TTP, as it negatively regulates apoptosis, inflammation, and cell growth to protect against damage due to stroke, neurodegeneration, and cardiovascular disease (Lubbers & Mohler, ; Seshacharyulu, Pandey, Datta, & Batra, ). Mahtani et al () reported the anti‐inflammatory effects of PP2A in rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Joe et al () suggested that TTP is effective at inducing inflammatory cytokines such as ILs and TNF‐α. PP2A may induce anti‐apoptotic and anti‐inflammatory activity in TTP, as it negatively regulates apoptosis, inflammation, and cell growth to protect against damage due to stroke, neurodegeneration, and cardiovascular disease (Lubbers & Mohler, ; Seshacharyulu, Pandey, Datta, & Batra, ). Mahtani et al () reported the anti‐inflammatory effects of PP2A in rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Many kinases have been implicated in the regulation of Ca 2+ transient, such as PKA, CamKII and PKC [47][48][49]. New findings highlight the role, overlooked for many years, of phosphatases in the fine tuning of the phosphorylation balance of physiologically relevant targets [45,50,51]. Protein phosphatases-1 (PP1) and -2A (PP2A) are responsible for the dephosphorylation of the majority (more than 90%) of phosphoserine/threonine residues in the cardiac cells [52].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…36 Reversible protein phosphorylation is essential for excitation-contraction coupling, Ca 2+ handling, cell metabolism, myofilament regulation, and cell-cell communication. 37 ~90% of dephosphorylation events are catalysed by just three phosphatases: PP1, PP2A and PP2B (calcineurin), all of which are regulated by microRNA we identified as changing after surgery. We identified multiple potential PP2A regulatory subunits potentially related to microRNA changes after surgery, which likely reflects the diversity of expression between cardiac cell types, subcellular domains, and disease phenotypes.…”
Section: Discussionmentioning
confidence: 97%
“…We identified multiple potential PP2A regulatory subunits potentially related to microRNA changes after surgery, which likely reflects the diversity of expression between cardiac cell types, subcellular domains, and disease phenotypes. 37 In the universal presence of a stressor phenotype after surgery, elevations in plasma troponin suggest that loss of cardioprotective mechanisms promote myocardial injury ( Figure 4D). An aberrant inflammatory response, as indicated by the decline in expression levels of the anti-inflammatory microRNA hsa-miR-146a-5p, is a plausible mechanism.…”
Section: Discussionmentioning
confidence: 99%